2019
DOI: 10.15835/nsb11110370
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic and Hypolipidemic Effects of Black Brand of Lipton Tea (Camellia sinensis) on Normal Male Albino Rats

Abstract: Recently, considerable attention has been focused on dietary supplements that possess hypoglycaemic and hypolipidemic properties in lieu of the synergistically synthesized drugs like statins and metiform which have been proven to have adverse effects. This present work was carried out to study the potential effects of Lipton tea aqueous extract (LTAE) on normal male albino rats. 36 six male Wistar rats weighing 115-150 g were assigned into four main groups; each group was divided into three subgroups, consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Studies on both human and animals have showed that tea consumption are associated with the blood lipid reduction and body weight loss. [9][10][11] Recently, considerable functional components were identied from tea, including polyphenols, 12 catechin, 13 EGCG and caffeine, 14 which are involved in promoting cholesterol reverse transport 15 through regulating key transcription factors of lipid metabolism 16 and activating lipid catabolism in liver. 17 Some reports have found that caffeine in tea was able to promote lipolysis in adipocytes, and it worked with catechins to inhibit triglyceride accumulation and adipocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on both human and animals have showed that tea consumption are associated with the blood lipid reduction and body weight loss. [9][10][11] Recently, considerable functional components were identied from tea, including polyphenols, 12 catechin, 13 EGCG and caffeine, 14 which are involved in promoting cholesterol reverse transport 15 through regulating key transcription factors of lipid metabolism 16 and activating lipid catabolism in liver. 17 Some reports have found that caffeine in tea was able to promote lipolysis in adipocytes, and it worked with catechins to inhibit triglyceride accumulation and adipocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%